New Zealand blackcurrant extract enhances fat oxidation during prolonged cycling in endurance-trained females - Strauss, J. A.; Willems, M. E.; Shepherd, S. O. (European Journal of Applied Physiology, 2018)
Purpose: New Zealand blackcurrant (NZBC) extract has previously been shown to increase fat oxidation during prolonged exercise, but this observation is limited to males. We examined whether NZBC intake also increases fat oxidation during prolonged exercise in females, and whether this was related to greater concentrations of circulating fatty acids. Methods: In a randomised, crossover, double-blind design, 16 endurance-trained females (age: 28 ± 8 years, BMI: 21.3 ± 2.1 kg/m², VO2max: 43.7 ± 1.1 ml/kg/min) ingested 600 mg·day-1 NZBC extract (CurraNZ™) or placebo (600 mg/day microcrystalline cellulose) for 7 days. On day 7, participants performed 120 min cycling at 65% VO2max, using online expired air sampling with blood samples collected at baseline and at 15 min intervals throughout exercise for analysis of glucose, NEFA and glycerol. Results: NZBC extract increased mean fat oxidation by 27% during 120 min moderate-intensity cycling compared to placebo (P = 0.042), and mean carbohydrate oxidation tended to be lower (P = 0.063). Pre-exercise, plasma NEFA (P = 0.034) and glycerol (P = 0.051) concentrations were greater following NZBC intake, although there was no difference between conditions in the exercise-induced increase in plasma NEFA and glycerol concentrations (P > 0.05). Mean fat oxidation during exercise was moderately associated with pre-exercise plasma NEFA concentrations (r = 0.45, P = 0.016). Conclusions: Intake of NZBC extract for 7 days elevated resting concentrations of plasma NEFA and glycerol, indicative of higher lipolytic rates, and this may underpin the observed increase in fat oxidation during prolonged cycling in endurance-trained females.